2020
DOI: 10.4103/ajts.ajts_40_19
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic disease of the fetus and newborn due to multiple alloantibodies in pregnancy

Abstract: Immune hemolytic disease of the fetus and newborn is a condition in which there is the premature destruction of fetal or neonatal red cells due to maternal alloantibody against red cell antigen inherited from father. We report the case of Hemolytic disease of fetus and newborn (HDFN) due to anti-E and anti-Fya antibody. Blood grouping was done using the conventional tube technique. Rh and Kell phenotyping of the patient and her husband performed by column agglutination and Duffy phenotyping were done by the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Furthermore, RBCs destruction begins in intrauterine life (12), which causes severe anaemia and neonatal jaundice or even extreme consequences, such as severe brain damage (13). According to , 50% of all foetuses with various aetiologies of HDN died of kernicterus or hydrop foetalis before 1945 (14). The lifespan of the infants' RBCs was shortened as a reaction of maternally cross foreign antibodies being transferred via the placenta and directed against paternally inherited antigens on the RBC.…”
Section: Clinical Manifestationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, RBCs destruction begins in intrauterine life (12), which causes severe anaemia and neonatal jaundice or even extreme consequences, such as severe brain damage (13). According to , 50% of all foetuses with various aetiologies of HDN died of kernicterus or hydrop foetalis before 1945 (14). The lifespan of the infants' RBCs was shortened as a reaction of maternally cross foreign antibodies being transferred via the placenta and directed against paternally inherited antigens on the RBC.…”
Section: Clinical Manifestationmentioning
confidence: 99%
“…In Malaysia, statistics have shown that anti-E is the second most common clinically significant antibody (37) in terms of HDN. The development of anti-E alloantibody can be frequently seen in pregnancies and is associated with HDN with mild to moderate progression (14).…”
Section: Rh Incompatibilitymentioning
confidence: 99%